Quantitative ethno-medicinal study of therapeutic flora found in Bunkure, Kano State Nigeria - Pandey, Abhishek Kumar; Yusuf Uba, Tasiu; Bux, Faiz; Yahaya, Musa Auwal; Ado Gezawa , Salisu (Ethnobotany Research and Applications, 2025)
Background: Obtaining medicines from the plant is an ancient tradition worldwide. This study aimed to collect the ethnomedicinal understanding of therapeutic plants from the indigenous communities of Bunkure, a Kano State, Nigeria region. Methods: A semi-structured interview using a validated questionnaire was applied to assess the valuable information from 200 participants (133 male and 67 female). Quantitative analysis of data was performed using Relative Frequency of Citation (RFC), Informant Consensus Factor (ICF), Use Value (UV), Jaccard Index, Direct Matrix Ranking, and Preference Ranking Exercise. Results: 74 plant species belonging to 38 families and 63 genera were recorded in this region and used here for ethnomedicinal purposes. Leaves (42.5%) are the most favourable portion of the plant used for ethnomedicine followed by the stem (33%), roots (11.5%), seeds (11%), and fruits (2%). High levels of relative frequency of citation (RFC) were found for Senna tora (0.06), Tamarindus indica (0.03), Ziziphus tripartite (0.03), Psidium guajava (0.01), Parkia biglobosa (0.01), Eucalyptus tereticornis (0.02), Anogeissus leiocarpus (0.02), and Allium sativum (0.03). Azadirachta indica (Neem) and Anogeissus leiocarpus stood out for their cultural and medicinal significance. Anogeissus leiocarpus is highly valued in Hausa culture for treating malaria, high fever, and boosting immunity. Neem, known for its antibacterial and antifungal properties, is a cornerstone in traditional medicine, commonly used for skin conditions, infections, stomach disorders, and malaria fever. Conclusion: The study underscores the threat to plant biodiversity and traditional medical knowledge due to the decline of therapeutic plants, largely driven by human activities. It highlights the vital role of herbal remedies, especially in underdeveloped regions with limited access to modern medicine. The research shows that a wide range of healing herbs is used to treat ailments, with traditional knowledge deeply embedded in daily life. However, this knowledge varies by demographics such as age, rural versus urban residence, and informant type. The study calls for more research into the antibacterial properties and toxicity of these plants to build community trust and protect natural habitats. Despite their ongoing use, these medicinal plants are increasingly at risk from deforestation and overharvesting. The study concludes that protecting and sustainably managing therapeutic plant species and preserving indigenous herbal knowledge are essential. Keywords: Ethnomedicine, Ailments, Plants, Administration route, Bunkure.